A NOVEL GABAERGIC DIETARY SUPPLEMENT ENHANCES SLEEP QUALITY IN OVARIECTOMIZED MICE - Bernsley, Devon; Şahin, Kazım; Kilic, Ertugrul; Korkusuz, Ahmet Kayhan; Orhan, Cemal; Er, Besir; Komorowski, James (Oxford Univ Press Inc, 2024)
[Abstract Not Available]
38th Annual Meeting of the Associated-Professional-Sleep-Societies (APSS) -- JUN 01-05, 2024 -- Houston, TX